RESILIENT LINERS IN DENTISTRY –A REVIEW - T, Priyadarsini; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
To review the composition, classification and other functions of resilient liners. Relining is the procedure used to resurface the tissue side of the removable dental prosthesis with a new base material, thus, producing an accurate adaptation the denture foundation area. The viscoelastic and elastic property of tissue conditioners result in an even distribution of load on the underlying mucosa and the cushioning of the cyclic forces of mastication. Denture soft lining materials liner materials have been used to provide cushion between the denture base and the supporting tissues and allow for more uniform distribution of stresses at the mucosa/tissues interface, as well as it help in better distribution of the occlusal forces.